Pengembangan Teknologi Pendidikan dalam Penggunaan Media Pembelajaran - Frezy Paputungan; Evandri Paputungan (LPPM UNiversitas Bina Mandiri Gorontalo, 2023)
The development of science and technology that is happening is increasingly advanced, making someone inevitably have to be ready to follow it. Likewise with an educator. Educators must understand how to use existing technology so that learning runs smoothly. In Law no. 20 of 2003 concerning National Education, it is stated that national education functions to develop abilities and form dignified character and national civilization in order to educate the nation's life, also aims to develop the potential of students so that they are able to become human beings who believe and fear God Almighty. , have noble character, be creative, be independent, and be a democratic and responsible citizen.